Relationship Body Massa Indeks (BMI) Towards Primary Dismenorrhoe : in Adolescents - Astuti, Anjar Tri; Irma Pratiwi, Putu (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2021)
Primary dysmenorrhoea is a health problem experienced by women of reproductive age with a fairly large morbidity rate. Primary dysmenorrhoea is a symptomatic phenomenon including abdominal pain, cramps and back pain that occurs in the first 24-36 hours of menstruation. Primary dysmenorrhea can cause various health problems that can affect daily activities, such as academic performance, household chores, work or working time.The purpose of this study was to determine the relationship between Body Massa Indeks (BMI) on primary dysmenorrhea in female adolescents. The design of this study used a cross sectional approach to determine the variables from one another. The sampling technique in this study was total sampling, where the total number of students in the D III Midwifery Study Program of the Ganesha Education University. Methods of data analysis using the chi square test on the SPSS 25 application. The results of data analysis obtained p value 0.159 (Î± = 0.05), indicating that there is no relationship between BMI and primary dysmenorrhea in adolescent girls in Prodi D III Midwifery, Ganesha University of Education. From the research results, young women are expected to do physical activity and light exercise as well as relaxation for pain and stress management. Keywords: Primary dysmenorrhoea, Body Massa Index, Young Girls